The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/solids2010004
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Doped-MgAl Superhydrophobic Layered Double Hydroxide for Enhanced Corrosion Resistance Properties

Abstract: Double doped layered double hydroxide thin films were developed directly on the aluminum substrate in two steps: Initially cerium-based MgAl-layered double hydroxide (LDH) were synthesized directly on the anodic aluminum surface via the in situ growth method, and were then modified with the stearate anions through an ion-exchange mechanism to achieve compact multifunctional protective thin films. The structural and morphological characteristics of the developed LDH films were investigated, and the surface cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The CoAl-LDHs-S characteristics make an attractive option for anticorrosion thin films; however the photocatalytic properties for the destruction of organic specks of dirt also need to be address. Due to higher surface roughness, the CoAl-LDHs-S formed a possible air film on the surface, which acted an additional barrier layer for the LDH thin film in contact the corrosive solution [19]. For practical applications, long-term superhydrophobicity plays an important role, so the change of water contact angle measurements was monitored while in continuous contact with 0.1 M NaCl solution from 1 h to 720 h, as shown in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CoAl-LDHs-S characteristics make an attractive option for anticorrosion thin films; however the photocatalytic properties for the destruction of organic specks of dirt also need to be address. Due to higher surface roughness, the CoAl-LDHs-S formed a possible air film on the surface, which acted an additional barrier layer for the LDH thin film in contact the corrosive solution [19]. For practical applications, long-term superhydrophobicity plays an important role, so the change of water contact angle measurements was monitored while in continuous contact with 0.1 M NaCl solution from 1 h to 720 h, as shown in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…The former coatings clean themselves by rolling water droplets that carry away dirt contaminations, and the latter coating approach chemically breaks down the absorbed dirt particles in the sunlight and results in a clean surface [23]. The superhydrophobic self-cleaning characteristics and improved corrosion-resistance properties of LDHs on aluminum surfaces are already well reported by various research groups [11,19,24,25]. However, the protective performance of photocatalytic LDH materials has not yet been investigated to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anionic exchange of LDH is based on different key parameters like electrostatic and hydrogen bonding between mixed metal hydroxide layers and interspatial anions . There are also certain parameters to be taken into consideration before performing the anion exchange process; affinity between the anions and hydroxide layers is one of them. , Scientists have claimed that the equilibrium constant for an anion exchange reaction is inversely proportional to the radius of the bare anion, which means that the smaller the anion radius is, the higher the charge density is, and the more favorable it is for exchange reaction . Various equilibrium constants for various exchange reactions are calculated, and the order of affinity of LDH for different anions is mentioned below. Monovalent ions < Divalent ions < Trivalent ions < Tetravalent ions PO 4 3 > CO 3 2 > SO 4 2 > OH > normalF > Cl > NO 2 > NO 3 > normalI Monovalent ions: .25em OH > normalF > Cl > Br<...…”
Section: Recent Advancements In Water Electrolysismentioning
confidence: 99%
“…In this context, the use of fatty acids, including myristic acid (CH3-(CH2)12-COOH), stearic acid (CH3-(CH2)16-COOH), or decanoic acid (CH3-(CH2)8-COOH) could represent an attractive more environmentally friendly route [35]. Iqbal et al [36] used 0.01 M sodium stearate solution at 50 °C for 5 h to develop the superhydrophobic structure over Ce doped MgAl LDH grown directly on an anodized AA6082 surface, which exhibited a water contact angle of 155°. It has been shown that the obtained layers presented superior corrosion resistance characteristics in 0.1 M NaCl, also benefitting from the synergic effect of cerium inhibitors and superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%